The impact of development finance institutions on the growth of Small and Medium Enterprises in Windhoek, Namibia - Hasheela, Sem (Research of GSB, 2018)
Small and Medium Enterprises play a very big role in an economy by creating jobs and value addition. There is no universal definition of Small and Medium Enterprises. Despite this important role, Small and Medium Enterprises are faced by numerous challenges such as lack of access to finance among several others. To circumvent this challenge Namibia has developed Development Financial Institutions namely Development Bank of Namibia as well as Small and Medium Enterprise Bank to ease the access to funding. Development Finance Institutions are established to finance the projects or activities that commercial banks may shy away. The establishment of these two institutions is supposed to result in significant growth and increase of the Small and Medium Enterprises in Namibia economy. This study therefore investigates the impact of these institutions in supporting the growth of Small and Medium Enterprise. The research used a case study research strategy that followed a descriptive-exploratory research design. The sample of eighty participants that were drawn from the Small and Medium Enterprises that were duly registered with the Ministry of Industrialisation, Trade and Small and Medium Enterprises Development. Data analysis was done by means of descriptive statistics such as tables, frequencies and percentages. Data analysis showed that, access to finance is a key obstacle towards the development of Small and Medium Enterprises in Windhoek as development finance institutions are approving relatively a small number of Small and Medium Enterprises. Recommendations were also made in relation to what needs to be done to ensure that Small and Medium Enterprises grow and development in viable ventures. Thus, the paper therefore suggested that the loans should be more affordable for the Small and Medium Enterprises to acquire necessary equipment. The Small and Medium Enterprises also need to approach Development Finance Institutions to access funds available. The growth of the bank's loan book has showed a growth in access to funding among the Small and Medium Enterprises.